Edukasi Penerapan Google Form Sebagai Alat Penilaian Pembelajaran di SDN 26 Palu Melalui Program Kampus Mengajar - Putra, Exsa; Ali , Zaenudin (Jurusan Ilmu Pendidikan - Universitas Lampung, 2024)
This dedication is motivated by the activities of the Teaching Campus Batch 5 which is a form of implementing the Merdeka Learning Campus Merdeka (MBKM) program from the Ministry of Education. This program is based on the ineffective implementation of learning carried out at the present time. This can be seen from the decrease in students' interest in learning, the level of understanding of students when learning, and students' literacy and numeracy abilities. Based on these problems affect the effectiveness of the learning process, one of which is at SDN Negeri 26 Palu. One of the methods used in community service is in the form of literacy and numeracy habituation activities. The end result of this activity is literacy and numeracy habituation for students at SD Negeri 26 Palu and increasing the real role and contribution of tertiary institutions and students in national development.